Role of T Cells in Chikungunya Virus Infection and Utilizing Their Potential in Anti-Viral Immunity - Poh, Chek Meng; Chan, Yi-Hao; Ng, Lisa F. P. (Frontiers in Immunology, 2020)
Chikungunya virus (CHIKV) is an arthropod-borne alphavirus that causes hallmark debilitating polyarthralgia, fever and rash in patients. T cell-mediated immunity, especially CD4+ T cells, are known to participate in the pathogenic role of CHIKV immunopathology. The other T cell subsets, notably CD8+, NKT and gamma-delta (γδ) T cells, can also contribute to protective immunity, but their effect is not actuated during the natural course of infection. This review serves to consolidate and discuss the multifaceted roles of these T cell subsets during acute and chronic phases of CHIKV infection, and highlight gaps in the current literature. Importantly, the unique characteristics of skin-resident memory T cells are outlined to propose novel prophylactic strategies that utilize their properties to provide adequate, lasting protection.